Antisense-derived HIV-1 cryptic epitopes are not major drivers of viral evolution during the acute phase of infection - Peng, B; Carlson, J; Liu, M; Gao, F; Goonetilleke, N; McMichael, A; Borrow, P; Gilmour, J; Heath, S; Hunter, E; Bansal, A; Goepfert, P (American Society for Microbiology, 2018)
While prior studies have demonstrated that CD8 T cell responses to cryptic epitopes (CE) are readily detectable during HIV-1 infection, their ability to drive escape mutations following acute infection is unknown. We predicted 66 CE in a Zambian acute infection cohort based on escape mutations occurring within or near the putatively predicted HLA-I restricted epitope. The CE were evaluated for CD8 T cell responses in patients with chronic and acute HIV infection. Of the 66 predicted CE, 10 were recognized in 8/32 and 4/11 patients with chronic, and acute infection respectively. The immunogenic CE were all derived from a single antisense reading frame within pol. However, when these CE were tested using longitudinal study samples, CE specific T cell responses were detected but did not consistently select for viral escapes. Thus, while we demonstrated that CE are immunogenic in acute infection, the immune responses to CE are not major drivers of viral escape in the initial stages of HIV infection. This latter finding may be due to either the subdominant nature of CE-specific responses, the low antigen sensitivity, and magnitude of CE responses during acute infections.